Ethical aspects of risk communication. (October 2016) - Shanmugaratnam, Shiva H.; Edwards, Adrian
Abstract: Clinical decision-making is becoming increasingly complex because of greater patient access to information, more clinical options and the emphasis on patient-centred care with informed decision-making. Risk communication should form part of evidence-based clinical practice, and it is important to think about what happens when clinicians adopt different consultation approaches. In this article, the ethical consequences of risk communication are analysed by looking at how the paternalistic and shared decision-making models of consultation demonstrate different ethical implications, based around a clinical scenario. To do this, we have applied the ethical principles of autonomy, utility and justice to these models. We show that the different models of consultation place varying degrees of emphasis on risk communication, patient autonomy and biomedical utility. This has implications for the way care is delivered both for the individual patient and for the population as a whole.